Correlation between Health Service Quality, TB Patient Behavior, and Treatment Compliance - Syahadat, Dilla Srikandi; Buchair, Nur Hikmah; Sari, Nur Fadhilah; Azzahra, Nur Azizah (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Tuberculosis (TB) remains a major public health problem in Indonesia, where treatment adherence is essential for preventing drug resistance, treatment failure, and continued transmission. The quality of health services and patient behavior are key determinants influencing adherence, particularly at the primary healthcare level.Objective: To analyze the effect of health services and tuberculosis (TB) patients’ behavior on adherence to TB treatment in Palu City.Methods: A cross-sectional study was conducted among 100 TB patients attending 14 community health centers (Puskesmas) in Palu City, Indonesia, selected through cluster random sampling. Data were collected from August to September 2024 using structured questionnaires. Univariate and bivariate analyses were performed, with statistical testing conducted using the Spearman rank correlation at a 95% confidence level (α = 0.05).Results: Most respondents were from Talise Health Center (12%), aged 21–29 years (24%), self-employed (50%), and had completed high school education (45%). Overall, 84% were treatment-compliant, and 97% demonstrated a positive attitude. All respondents with a less favorable attitude were non-compliant, while 86.6% of those with a good attitude were compliant. Regarding health services, 96% reported good services, and 86.5% of them were compliant, compared to 25% among those with poor services. Significant associations were found between attitude (ρ = 0.000, r = 0.417), health service quality (ρ = 0.000, r = 0.455), and treatment adherence.Conclusion: There is a significant association between the quality of healthcare services, patient attitudes, and adherence to TB treatment. Strengthening patient-centered services and ongoing counseling at Puskesmas are essential to sustain treatment success and reduce transmission.